Ultrafast changes of magnetic anisotropy driven by laser-generated coherent and noncoherent phonons in metallic films - Kats, V.N.; Linnik, T.L.; Salasyuk, A.S.; Rushforth, A.W.; Wang, M.; Wadley, P.; Akimov, Andrey V.; Cavill, S.A.; Holy, V.; Kalashnikova, A.M.; Scherbakov, A.V. (American Physical Society, 2016)
Ultrafast optical excitation of a metal ferromagnetic film results in a modification of the magnetocrystalline anisotropy and induces the magnetization precession. We consider two main contributions to these processes: an effect of noncoherent phonons, which modifies the temperature dependent parameters of the magnetocrystalline anisotropy and coherent phonons in the form of a strain contributing via inverse magnetostriction. Contrary to earlier experiments with high-symmetry ferromagnetic structures, where these mechanisms could not be separated, we study the magnetization response to femtosecond optical pulses in the low-symmetry magnetostrictive galfenol film so that it is possible to separate the coherent and noncoherent phonon contributions. By choosing certain experimental geometry and external magnetic fields, we can distinguish the contribution from a specific mechanism. Theoretical analysis and numerical calculations are used to support the experimental observations and proposed model.